Preisach modeling on temperature dependent mean-field ising-hysteresis - Teerawat Monnor (2018)
In this work, the Preisach technique was employed to characterize temperature dependent hysteresis loops extracted from the Ising model considered under the mean-field (MF) framework. In constructing the Preisach densities for these MF loops, a stochastic process was used to optimize the hysterons weight. Then, from the obtained Preisach densities, series of the MF hysteresis loops were accurately re-constructed, and the temperature independence of densities was observed. In addition, an increase of reversible polarization and a decline of irreversible polarization with increasing temperature were evident. These phenomena were examined and found to be caused by the enhancement of thermal fluctuation at higher temperature, which alleviates the spin flipping viscosity and lessens the phase-lag in hysteresis characteristic. © 2014 Taylor and Francis Group, LLC.